Physiotherapy protocol with interferential current in the treatment of vaginismus - Observational and prospective study - Pereira, Carla Maria de Abreu; Ambrosio, Ricardo Thiago Paniza; Borges, Erica Maximiano Costa Mantelli; Lima, Sônia Maria Rolim Rosa; Alves, Vera Lúcia dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Vaginismus is characterized by involuntary recurrent or persistent contraction of the perineum muscles adjacent to the lower third of the vagina when vaginal penetration with penis, finger, tampon or speculum is attempted. However, there may be low adherence to the therapy due to the need of the touch of the perineal region by the therapist. The interferential current can be an alternative, once it can be used externally and superficially. Objective: To evaluate a clinical protocol with the use of interferential current to treat vaginismus and to observe the decrease of pain and the behavior of the electrical activity on the perineal musculature. Methods: The protocol was registered in the Clinical Trials (NCT03176069) and it was approved by the Research Ethics Committee (CAAE: 51995515.4.0000.5479). This will be a controlled clinical trial with a group of patients with Vaginismus (n = 30) and another without (n = 30). All women will be submitted to evaluation and reassessment with algometry, electromyographic biofeedback and visual analogue pain scale. The vaginismus group will perform 10 sessions, twice a week, with the interferential current (frequency = 2000 Hz, modulated amplitude = 80 Hz, pulse width = 200 μs and intensity according to sensory level) for 30 minutes. The evolution of vaginismus group before and after the intervention and the correlations between groups will be statistically analysed with the t Student’s or the Mann-Whitney test with a significance level of 5% (p ≤ 0.05). Hypothesis: This protocol will present a possible alternative for the treatment of vaginismus and it will investigate the electrical activity of the pelvic floor musculature in vaginismus compared to women who do not suffer from this disorder. It is expected to decrease the pain, to measure the muscular electrical activity before and after the intervention in the vaginismus group and to investigate the muscular electrical activity in the group without sexual dysfunction.